2008
DOI: 10.2134/jeq2007.0574
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Monomer Leaching from Polyacrylamide‐Treated Irrigation Furrows

Abstract: Water-soluble anionic polyacrylamide (WSPAM), which is used to reduce erosion in furrow irrigated fi elds and other agriculture applications, contains less than 0.05% acrylamide monomer (AMD). Acrylamide monomer, a potent neurotoxicant and suspected carcinogen, is readily dissolved and transported in fl owing water. Th e study quantifi ed AMD leaching losses from a WSPAM-treated corn (Zea mays L.) fi eld using continuous extraction-walled percolation samplers buried at 1.2 m depth. Th e samplers were placed 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
(34 reference statements)
3
28
1
4
Order By: Relevance
“…We exclude from consideration numerous advertising information about the stability of SSHP in soils for 5-6 years or more, because in our opinion they are not correspond to reality. Lentz et al [40] reports a rather slow biodegradation of PAA not more than 10% yr - obtained in this work and previous publication [5].…”
Section: Biodegradation Of Synthetic Hydrogels and Their Componentssupporting
confidence: 79%
See 1 more Smart Citation
“…We exclude from consideration numerous advertising information about the stability of SSHP in soils for 5-6 years or more, because in our opinion they are not correspond to reality. Lentz et al [40] reports a rather slow biodegradation of PAA not more than 10% yr - obtained in this work and previous publication [5].…”
Section: Biodegradation Of Synthetic Hydrogels and Their Componentssupporting
confidence: 79%
“…Reverse positive relationship of biodegradation with temperature increases peat decomposition under local greenhouse effect conditions [37,38]. For cities such a factor may be the so-called "urban heat island" [26,40]. In this case, the period of biological activity is prolonged for the cold season and biodegradation of peat during winter thaws can reach 20-25% of average annual losses (see "Results").…”
Section: Dependence Of Biodegradation Rate On Soil Depth and Nomograpmentioning
confidence: 99%
“…Polyacrylamide has been used safely to reduce erosion in furrow crops for many years and it is estimated that in the United States approximately 1 million ha is PAM treated (Sojka et al, 2007). Application of PAM at concentrations ranging from 1 to 10 mg L −1 is recommended by USDA−NRCS for reducing soil erosion in furrow‐irrigated crops (Lentz et al, 2008). However, in recent years, concerns about toxicity of PAM have been expressed because PAM contains small amounts of acrylamide monomer (AMD) as an impurity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exposure levels required to cause neurotoxic or carcinogenic effects in humans are several orders of magnitude above that conceivable from exposures resulting from current application levels. Anionic PAM containing <0.05% AMD has a low toxicity and is considered safe (Sojka et al, 2007; Lentz et al, 2008 Weston et al, 2009). Furthermore, studies have shown that PAM degrades in soil at rates >10% yr −1 and does not revert back to AMD on degradation (Sojka et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The surface soil is a silt loam, with 10 to 13 g kg −1 organic C, 5% calcium carbonate equivalent, and a pH of 7.7 (saturated paste). We aligned the experimental plots with previously installed soil water percolation samplers (Lentz et al, 2008). Plots were planted to silage corn in the first (2003) and second growing seasons and to barley ( Hordeum vulgare L.) in the third and fourth growing seasons.…”
Section: Methodsmentioning
confidence: 99%